Analisis Variabel-variabel Anteseden dan Konsekuensi Organizational Professional Conflict Akuntan di KAP dan Industri - Jantje Eduard Lekatompessy (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to examine antecedents of accountants perceived organizational-professional conflict (OPC) and its consequences. Affective, continuance, dan professional commitments are hypothesized to be antecedents of OPC, while job satisfaction, job-related tensions, and turnover intentions are the consequences of OPC.The sampling method is convenience sampling. The respondents are accountants working in public accounting firms and industry. Data were collected by mail survey and personal contact. There were 278 respondents participated in this research. Data analysis used Structural Equation Modeling.The results of this study show that affective, continuance, and professional commitments are antecedents of OPC and they have significant negative effect on OPC. OPC has significant negative effects on job satisfaction, positive on job-related tensions and turnover intentions.